Embedded design using programmable gate arrays - Silage, Dennis, ....- (Gilroy : Bookstand, 2008)
Embedded Design Using Programmable Gate Arrays Dennis Silage This text describes modern embedded processing systems using the Field Programmable Gate Array. This new paradigm in embedded design utilizes the Verilog Hardware Description Language behavioral synthesis of controller and datapath constructs and the Finite State Machine for Digital Signal Processing, communications and control with the FPGA, external hard core peripherals, custom internal soft core peripherals and the soft core processor. Review materials and references for DSP place the embedded design projects in perspective. This text features the Xilinx Spartan-3E Starter Board, the Xilinx ISE WebPACK EDA, Xilinx LogiCORE blocks and the Xilinx PicoBlaze soft core processor. Embedded Design Using Programmable Gate Arrays is intended as a supplementary text and laboratory manual for undergraduate students in a contemporary course in digital logic and embedded systems. Professionals who have not had an exposure to the fine grained FPGA, the Verilog HDL, an EDA software tool or the new paradigm of the controller and datapath and the FSM will find that this text and the Xilinx Spartan-3E Starter Board provides the necessary experience in this emerging area of electrotechnology.
Keywords: Computer ; hardware